Positive Antithyroid Antibodies and Nonsuppressed TSH Are Associated with Thyroid Cancer: A Retrospective Cross-Sectional Study - Jan Krátký; Jana Ježková; Mikuláš Kosák; Hana Vítková; Jana Bartáková; Miloš Mráz; Jindřich Lukáš; Zdenka Límanová; Jan Jiskra (International Journal of Endocrinology)
The relationship between Hashimoto’s thyroiditis (HT) and thyroid cancer (TC) is a controversial topic; it remains unclear if HT acts as a risk factor of TC. The aim of our study was to compare the presence of HT and thyroid function in patients with TC and benign nodules. We analyzed 2571 patients after fine needle aspiration biopsy of thyroid nodule. Totally, 91 patients with primary TC and 182 sex- and age-matched controls were included. Positive antithyroid peroxidase (anti-TPO) and antithyroglobulin (anti-Tg) antibodies were associated with TC (anti-TPO 44% in TC vs. 27% in controls, P=0.005, anti-TG 35% in TC group vs. 21% in controls, P=0.018), and the TC group had significantly higher TSH (median 1.88 mIU/l vs. 1.21 mIU/l, P<0.001). Using multiple logistic regression, positive anti-TPO was identified as an independent risk factor (OR 2.21, P=0.018), while spontaneously suppressed TSH<0.5 mIU/l was a protective factor (OR 0.3, P=0.01) against TC. In conclusion, nodules in subjects with positive antithyroid antibodies could be considered to have a higher risk of malignancy. However, based on our results, it is not possible to declare that TC is triggered by HT.